How Well Does Google Translate, Translate from English to Indonesian? - Farida Repelita Waty Kembaren; Jauharah Jilan Situmorang; Liyundzira Fikroh Gani (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this study is to use matching techniques and language mistake analysis to figure out how accurate Google Translate is, especially when translating text from English to Indonesian. As a source text, one passage from Johann Gottfried Herder's book